Determinasi Perilaku Konsumtif Mahasiswa Di Kota Palangka Raya: Peran Self Control Dalam Mengurangi Konsumsi Berlebihan - Solikah Nurwati; Zainal Firdaus Wardhana (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Students are a productive age group who are often the main target of marketing trendy, branded, and fashionable products through social media that are personal and persuasive. This condition encourages the emergence of consumptive behavior as a form of fulfilling a lifestyle to appear attractive. This study uses a qualitative method quantified through a Likert scale (1–5) with a Google Form survey, conducted in June 2025 among active students in Palangka Raya City. From a population of 37,504 students, 350 respondents were obtained through a purposive sampling technique. Data analysis with Smart PLS 4.0. The results of the study: the contribution of financial literacy, lifestyle and self-control simultaneously to consumptive behavior is 72.4% (strong category), while financial literacy and lifestyle influence self-control by 13.6% (weak category). There is a negative correlation between financial literacy and self-control to consumptive behavior, but a positive correlation by lifestyle. Self-control is proven to be a link between financial literacy and consumptive behavior. Even though students have good self-control, exposure to a consumerist lifestyle can still encourage the emergence of consumerist behavior.